1996
DOI: 10.1103/physrevd.54.5620
|View full text |Cite
|
Sign up to set email alerts
|

Average kinetic energy of a heavy quark in semileptonicBdecay

Abstract: Within the ACCMM model the average kinetic energy of heavy quark in a heavy-light meson is calculated as hp, solely from the fact that the Gaussian momentum probability distribution has been taken in the ACCMM model. Therefore, the Fermi momentum parameter p F of the ACCMM model is not a truly free parameter, but is closely related to the average kinetic energy of heavy quark, which is theoretically calculable in principle. In this context, we determine p F by comparing the theoretical prediction of the ACCMM … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
3
22
1
Order By: Relevance
“…For the study of the bound state properties of hadrons which contain both heavy and light quarks like B-meson, it is appropriate to use the relativistic quark model [12,21], which is a potential model approach with relativistic kinematics.…”
Section: Relativistic Quark Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For the study of the bound state properties of hadrons which contain both heavy and light quarks like B-meson, it is appropriate to use the relativistic quark model [12,21], which is a potential model approach with relativistic kinematics.…”
Section: Relativistic Quark Modelmentioning
confidence: 99%
“…However, Kapustin et al [11] showed later that this lower bound could be significantly weakened by higher order perturbative corrections. Previously we also calculated [12] the value of p 2 by applying the variational method to the relativistic Hamiltonian, and obtained p 2 = 0.44 GeV 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, we point out that the result −λ 1 = p 2 is characteristic of CQ models in which a non-relativistic interquark potential, which is more appropriate in case of heavy-heavy mesons, is adopted for the description of heavy-light mesons, as it has been done in Refs. [12,13] and [14]. The aim of this letter is indeed to show that in case of heavy-light mesons the CQ model (CQM) prediction for −λ 1 is sharply sensitive to relativistic effects in the CQ interaction, which may lead to substantial deviations from the non-relativistic expectation −λ 1 = p 2 .…”
mentioning
confidence: 99%
“…Refs. [12,13]). However, we point out that the result −λ 1 = p 2 is characteristic of CQ models in which a non-relativistic interquark potential, which is more appropriate in case of heavy-heavy mesons, is adopted for the description of heavy-light mesons, as it has been done in Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation